Android Based Activity Information Application in Surabaya - Tommy Nuril Huda; Pamudi; David Hermansyah (Jurnal Ilmiah Informatika dan Komputer, 2025)
Surabaya is the capital of East Java which also became the second metropolitan city after Jakarta. As one of the largest cities in Indonesia, Surabaya often holds major events. During the past year counted already dozens or even hundreds of activities held in Surabaya. Usually events are held in order to commemorate the anniversary of the city and other celebrate. The usual events include cultural fairs, culinary festivals, and job fair. Android is an open source operating system that allows software to be freely modified and distributed by device makers and app developers. Therefore the author has the idea to utilize android technology as one of the media information by creating an application. This application is made to publish an events to be held in Surabaya, which is titled "Application Information of Events in Surabaya Based Android".